INTERCULTURAL COMMUNICATION PATTERNS AND INHIBITING FACTORS IN MARRIAGE BETWEEN DIFFERENT COUNTRIES NIKMATUL ROSIDAH - Rahma Yanti; Shabri, Irsyad; Haq, Abdul Dinul (Prologue: Journal on Language and Literature, 2024)
This study aims to determine the pattern of intercultural communication and the inhibiting factors of the intercultural communication process in inter-ethnic marriages of Nikmatul Rasidah and her husband, Paul. The theory used is the theory of interpersonal communication. The method used in this study is qualitative with a descriptive approach, with data collection through interviews and direct observation. The research subject is Nikmatul Rasidah and Paul by using triangulation credibility test. Based on the results of research conducted, it is known: (a) the pattern of intercultural communication applied by this couple is tolerance, being open to each other, giving in to each other, telling each other, respecting, understanding, and learning the language of each other to maintain harmony in their household. (b) barriers to communication are influenced by differences in language, behavior and habits, cultural background, social prejudice or stereotypes.